Theory of Planned Behavior on the Determinants of Cosmetic Hormones Use to Overcome Gender Dysphoria among Transgenders in Yogyakarta, Indonesia - Destinady Kadiser Miden; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Gender dysphoria refers to discomfort or distress that is caused by a discrepancy between an individual’s gender identity and the gender assigned at birth (and the associated gender role and/or primary and secondary sex characteristics). Gender reassignment surgery is performed to change primary and/or secondary sex characteristics. For a male to female gender reassignment, surgical procedures may include genital reconstruction (vaginoplasty, penectomy, orchidectomy, clitoroplasty) and cosmetic surgery (breast implants, facial reshaping, rhinoplasty, abdominoplasty, thyroid chondroplasty (laryngeal shaving), voice modification surgery (vocal cord shortening), hair transplants). This study aimed to examine the determinants of cosmetic hormones among transgender in Yogyakarta, Indonesia, using Theory of Planned Behavior (TPB).Subjects and Method: This was a cross-sectional study carried out in Yogyakarta, Indonesia, in November 2018. A sample of 201 transgender was selected by snowball sampling and fixed disease sampling, consisting of 67 transgender using cosmetic hormone and 134 transgender not using the cosmetic hormone. The dependent variable was the use of cosmetic hormones. The independent variables were age, knowledge, education, intention, attitude, perceived behavioral control, and subjective norm. The data were collected by questionnaire and analyzed by path analysis.Results: Cosmetic hormone use was directly increased by strong intention (b= 1.65; 95% CI= 0.98 to 2.31; p<0.001), positive attitude (b= 1.15; 95% CI= 0.48 to 1.81; p= 0.001), but decreased by strong perceived behavioral control not to use cosmetic hormone (b= -1.02; 95% CI= -1.70 to -0.34; p=0.003). Cosmetic hormone use was indirectly affected by age, education, locus of control, attitude, perceived behavioral control, subjective norm, and social norm.Conclusion: Cosmetic hormone use is directly increased by strong intention, positive attitude, but decreased by strong perceived behavioral control not to use the cosmetic hormone. Cosmetic hormone use is indirectly affected by age, education, the locus of control, attitude, perceived behavioral control, subjective norm, and social norm.Keywords: cosmetic hormone, transgender, Theory of Planned BehaviorCorrespondence: Destinady Kadiser Miden. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email: destinady.kmiden@gmail.com. Mobile: 085328999232.Journal of Health Promotion and Behavior (2018), 3(3): 212-222https://doi.org/10.26911/thejhpb.2018.03.03.08